2020
DOI: 10.24099/vet.arhiv.0780
|View full text |Cite
|
Sign up to set email alerts
|

Blood metabolic profile and acid-base status of Istrian goats - a critically endangered Croatian goat - in relation to age

Abstract: The aim of the present research was to determine the blood metabolic profile and acid-base status of Istrian goats in a Mediterranean production system. The research was carried out on 28, non-gravid Istrian goats divided into four groups: group I-≤ 6 month old kids; group II-≤ 2 year old goats; group 3-from 2 to 5 year old goats; group IV->5 year old goats. The goats were grazing on extensive Mediterranean pastures, but when in the stall, they were fed with hay and approximately 0.2 kg corn per day, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 28 publications
5
12
1
Order By: Relevance
“…The data in Table 1 shows that the mean ALP activity of Aceh cattle in the 2-4-year-old age group (146.00±29.48 U/L) was higher and significantly different than the >4-6-year-old age group (94.37±41.99 U/L). These results are in accordance with studies that have been carried out on African buffaloes (Couch et al, 2017), goats (Gwaze et al, 2012;Antunović et al, 2020), and dogs (Brenten et al, 2016). All of these studies found that adult animals have lower ALP activity compared to young animals.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The data in Table 1 shows that the mean ALP activity of Aceh cattle in the 2-4-year-old age group (146.00±29.48 U/L) was higher and significantly different than the >4-6-year-old age group (94.37±41.99 U/L). These results are in accordance with studies that have been carried out on African buffaloes (Couch et al, 2017), goats (Gwaze et al, 2012;Antunović et al, 2020), and dogs (Brenten et al, 2016). All of these studies found that adult animals have lower ALP activity compared to young animals.…”
Section: Resultssupporting
confidence: 92%
“…Albumin concentrations were also higher in the age group >4-6 years old (4.52±0.40 g/dL) compared to the age group 2-4 years old (4.09±0.45) but not significantly different. This higher total protein concentration in the older age group is in accordance with studies that have been carried out on male cattle (Irfan, 2014), calves (Nagy et al, 2014;Souza et al, 2020), Brahman cattle (Kristanto and Widiyono, 2021), African buffaloes (Couch et al, 2017), goats (Antunović et al, 2020), donkeys (Sow et al, 2017), camels (Ahmadi-hamedani et al, 2014), dogs (Brenten et al, 2016;Lee et al, 2020), pigs (Yu et al, 2019), and broiler chickens (Tothova et al, 2019). Tothova et al (2016) stated that age is one of the most important factors that affect the concentrations of serum protein and its fractions (albumin and globulin).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The ELS and PSC diets did not influence the proportions of C6:0, C8:0 and C10:0, fatty acids responsible for the particular sensory properties of goats´ milk (Bessa et al, 2016) and health benefits providing better digestibility of goat milk (Zenebe et al, 2014). Bernard et al (2015) found that SCFA, specifically C6:0, C8:0 and C10:0, were lowered in milk when feeding goats with 216 g/kg DM of extruded linseed in goats´ diets Contains C18:1 t7 + t8 as a minor components, 2 Contains C18:1 t10 as a minor component, 3 Contains C18:1 t12 + t13 + t14 as a minor components, 4 Contains C18:1 c14 as a minor component, 5 Contains C19:0 a minor component, 6 Contains C18:2 t9 t12 + t8 c12 + c9 t13 a minor components; SEM-standard error of mean; a,b Row means with different superscripts differ significantly at P < 0.05 Proportions of stearic (C18:0), OA, vaccenic (VA, C18:1 t11) acid and CLA remained unaffected by dietary treatments. Bernard et al (2015) determined that addition of extruded linseed in combination with fish oil may be efficient in increasing VA and CLA proportions in milk.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, blood metabolic profile (BMP) is used to predict the emergence of some metabolic disorders, energy metabolism, and nutritional and health status in animals [13]. The indicators of BMP are mainly the hematochemical parameters, which are influenced by various factors, such as breed, age [14], gender [15], season [16], reproductive status [17], and infectious processes [18]. The most important biomarkers of energy metabolism are glucose (GLU), cholesterol (CHO), and triglycerides (TGs).…”
Section: Introductionmentioning
confidence: 99%